Sexual Violence in the Wattpad's Young Adult Novels: Feminist Studies - Septhi Andini Darmawan; H. Halimah (Journal of Feminism and Gender Studies, 2023)
Nowadays, Indonesia is one of country labeled as sexual violence emergency country. Literature can be medium to expressed writer’s view about sexual violence in society, Wattpad as a platform to publishing popular novels can be one of them. Some of Wattpad teen novels choosen sexual violence as a conflict, and it is related to fact that teenager or adolescence was prone to becomed sexual violence victims. This study aimed to describe how sexual violence represented in Wattpad teen novels. Feminist literary criticsm applied in this study, and it shows that not only patriarchy system caused sexual violence, but also caused by juvenile delinquency. Furthermore, the sexual violence solution in Wattpad teenlit represented that some of society has been concerned to victim’s perspective. Keywords : feminist literay criticism, sexual violence, teenlit, wattpad